2020
DOI: 10.3390/pathogens9040294
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Apoptin in Chicken Anemia Virus Replication

Abstract: Apoptin is the Vp3 protein of chicken anemia virus (CAV), which infects the thymocytes and erythroblasts in young chickens, causing chicken infectious anemia and immunosuppression. Apoptin is highly studied for its ability to selectively induce apoptosis in human tumor cells and, thus, is a protein of interest in anti-tumor therapy. CAV apoptin is known to localize to different subcellular compartments in transformed and non-transformed cells, depending on the DNA damage response, and the phosphorylation of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 96 publications
0
10
0
Order By: Relevance
“…The characterization of the NLSs and NESs of the ORF3 proteins ( Wang et al., 2004 ; Poon et al., 2005 ; Hough et al., 2015 ; Gu et al., 2016 ) has begun to shed light on the subcellular localization of ORF3 proteins, which contributes to their different apoptotic activities. Particularly for the CAV ORF3 protein, phosphorylation sites ( Rohn et al., 2002 ; Rohn et al., 2005 ; Lanz et al., 2012 ; Kucharski et al., 2016 ; Feng et al., 2020 ), such as Thr108, Thr107, Thr56, and Thr61, are considered to be of vital importance to its nuclear localization and apoptotic effect, whereas it has not yet been discovered in the ORF3 proteins of PCV and DuCV. On the other hand, the CAV ORF3 protein, in particular, has a tumor cell-specific nuclear targeting signal ( Danen-Van Oorschot et al., 2003 ; Kuusisto et al., 2008 ), which indicates tumor-selective toxicity induced upon its accumulation in the nuclei of transformed cells ( Danen-Van Oorschot et al., 1997 ; Poon et al., 2005 ; Helck et al., 2008 ; Zhao et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characterization of the NLSs and NESs of the ORF3 proteins ( Wang et al., 2004 ; Poon et al., 2005 ; Hough et al., 2015 ; Gu et al., 2016 ) has begun to shed light on the subcellular localization of ORF3 proteins, which contributes to their different apoptotic activities. Particularly for the CAV ORF3 protein, phosphorylation sites ( Rohn et al., 2002 ; Rohn et al., 2005 ; Lanz et al., 2012 ; Kucharski et al., 2016 ; Feng et al., 2020 ), such as Thr108, Thr107, Thr56, and Thr61, are considered to be of vital importance to its nuclear localization and apoptotic effect, whereas it has not yet been discovered in the ORF3 proteins of PCV and DuCV. On the other hand, the CAV ORF3 protein, in particular, has a tumor cell-specific nuclear targeting signal ( Danen-Van Oorschot et al., 2003 ; Kuusisto et al., 2008 ), which indicates tumor-selective toxicity induced upon its accumulation in the nuclei of transformed cells ( Danen-Van Oorschot et al., 1997 ; Poon et al., 2005 ; Helck et al., 2008 ; Zhao et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation confirmed that the DNA damage response (DDR) regulates the nuclear localization and apoptotic effect of CAV ORF3 through checkpoint kinase1/2 (Chk1/2), which is mediated by the phosphorylation of Thr56 and Thr61 during viral replication ( Kucharski et al., 2016 ; Feng et al., 2020 ). Upon induction of DNA damage, the ORF3 protein expressed in primary cells is translocated to the nucleus, but in transformed cells, the inhibition of DDR signaling results in the cytoplasmic localization of the protein ( Kucharski et al., 2011 ).…”
Section: The Regulation Of Orf3-induced Apoptosismentioning
confidence: 91%
“…There are some wellestablished viral examples of nuclear exports, exploited by matrix M1 protein of influenza A virus [40,41], E7 oncoprotein of human papillomavirus [40] and REV protein of HIV-1 [41]. Presence of both NLS and NES is also known for two viral proteins, VP1 and VP3 from the chicken anemia virus and using these signals and these proteins regulate the VP2 shuttling in cells [42,43]. Altogether, it is clear that with exploitation of these NLSs and NESs from the N protein become capable of shuttling between the cytoplasm and the nucleus, during the SARS CoV life cycle and plays an important role in the SARS CoV replication, assembly, and SARS CoV budding.…”
Section: Utilizing Iedb We Have Generated the Largest Epitome Inventomentioning
confidence: 99%
“…VP2 is an auxiliary scaffold protein required for CIAV assembly, which helps VP1 to form the correct conformation ( 4 ), and both VP1 and VP2 can cooperate with each other to induce an immune response. VP3 represents a functional protein of the virus, which is also known as apoptin ( 5 ) and studies have found that transfection of the VP3 gene into chicken monocyte cultures, can induce apoptosis, highlighting its importance in CIAV infection ( 6 ).…”
Section: Introductionmentioning
confidence: 99%